Training team problem-solving skills: an event-based approach. - Oser, R. L.; Gualtieri, J. W.; Cannon-Bowers, J. A. (Computers in Human Behavior)
Part of a special issue on computer-based performance assessment of problem solving. In light of the critical role of teams in the performance of many organizations, the development of training systems to support coordination and problem solving is vital. Advances such as computer-based performance assessment offer considerable promise for training; but introducing technology alone does not guarantee that training will be effective. Three important issues that must be taken into account when developing coordination and problem-solving training are how technology can best be used to provide an environment where learning can take place; the knowledge, attitudes, and skills that must be learned and trained in order to facilitate expert problem solving teams; and how the development of problem solving expertise can be fostered through a systematic instructional strategy. A naturalistic decision-making paradigm is used to provide a theoretical framework for describing the problem solving task domain; and an event-based approach to training is offered as a practical application for teams to perform in naturalistic environments.